HUBUNGAN HIPERURISEMIA DAN FRACTION URIC ACID CLEARANCE DI DESA TENGANAN PEGRINGSINGAN KARANGASEM BALI - Kurniari, Pande Ketut; Kambayana, Gde; Raka Putra, Tjokorda (journal of internal medicine; Vol. 12, No. 2 Mei 2011)
Hyperuricemia is a condition of high consentration of uric acid in the blood. In most epidemiology study hyperuricemia is defined as level uric acid more than 7.0 mg/dl in men and more than 6.0 mg/dl in women. Hyperuricemia can be caused by several factors. Regarding the etiology hyperuricemia can be classified as primary, secondary and idiopathic hyperuricemia. Primary hyperuricemia related to genetic factor while secondary hyperuricemia caused by condition or other factors besides genetic factor such as high purin consumption, chronic kidney disease, certain drugs, alcohol and hypertension. Hyperuricemia can be caused by inceased of uric acid metabolism (overproduction), decreased of urine uric acid excretion (underexcretion), or mix of both. Fraction Uric Acid Clearance (FUAC) is one of the method used to differentiate either hyperuricemia caused by overproduction or underexcretion. The aim of this studi is to determine the prevalence of hyperuricemia, means value of FUAC and association between hyperuricemia and FUAC in Tenganan Pegringsingan Karangasem region Bali. A cross sectional analytic study was conducted on Balinesse in Tenganan Pegringsingan Karangasem region. Sample study was Balinese at age of 13 years old or above, agree to participate by informed consent. Descriptive statistic analysis on numeric data presented as mean mean ± SD, nominal and ordinal data in proportion. Pearson?s correlation method is used in comparing the correlation between hyperuricemia and FUAC. Of 100 eligible samples, mean age was 37.20 ± 13.59 y.o, 51 (51%) men and 49 (49%) women. Youngest age was 13 y.o and oldest was 69 y.o. Mean of blood uric acid level was 5.69 ± 1.43 mg/dl. Prevalence of hyperuricemia on this study was 28%, 21% men and 7% women. Means value of FUAC is 6.41 + 1.99%; 6.94 + 2.01% in normal uric acid level and 5.04 ± 1.1% in hyperuricemia. There is close correlation between hyperuricemia and FUAC (r = 0.43; p = 0.00)
Keywords: uric acid, hyperuricemia, FUAC